Electroacupuncture stimulation improves pulmonary fibrosis by modulating ferroptosis in rats: multiscale analysis of transcriptome and proteome - Yange Tian; Qinghua Song; Ruilong Lu; Yan Du; Zhiguang Qiu; Yixi Liao; Bo Wang; Jiansheng Li (Chinese Medicine)
Abstract Background Idiopathic Pulmonary fibrosis (IPF) is a progressive lung disease with poor survival. Electroacupuncture has been proven to improve dyspnea in IPF patients, but the mechanism remains unclear. Methods The IPF rat model was established by intratracheal instillation of bleomycin. Electroacupuncture was performed 3 times a week for 4 weeks. Lung function and lung histopathology were tested to evaluate the respiratory movements and lung damage. Collagen I (COL-I), α-smooth muscle actin (α-SMA) and hydroxyproline (HYP) were measured to evaluate fiber deposition. Characterization of gene and protein expression profiles in IPF rat was recognized by integrated proteomic and transcriptomic. WGCNA and GSEA were used to identify the key modules and signaling pathways of electroacupuncture against IPF. Results Electroacupuncture improved vital capacity, RI, Cdyn, the alveolar rupture and fibrous tissue deposition, and reduced the expression of α-SMA, COL-I, and HYP. 1104 differentially expressed genes and 391 proteins were identified which were reversed by electroacupuncture. Two modules were obtained and functional analysis showed ferroptosis, PI3K-AKT and FoxO signaling pathway were significantly enriched. Genes and proteins with strong correlations were screened out, and functional analysis showed ferroptosis and glutathione metabolism were significantly enriched. Electroacupuncture reduced the levels of Fe3+, Fe2+, LPO and MDA in the lung tissue of PF rats and increased the levels of GSH and SOD. Further, electroacupuncture improved the mitochondrial swelling of alveolar epithelial cells in PF rats. Also, electroacupuncture inhibited the level of p-Akt and p-FoxO3. Conclusions Electroacupuncture regulated ferroptosis to improve IPF via inhibiting PI3K-AKT and FoxO signaling.